Measurement and analysis of Chinese journal discriminative capacity. Issue 1 (February 2020) - Zhang, Baolong; Wang, Hao; Deng, Sanhong; Su, Xinning
Highlights: A new perspective to assess the academic journal based on the difference of research content is proposed. A novel method for measuring and analyzing the discriminative capacity among journals is provided. This method can be used to detect the journals with distinctive or homogeneous characteristics. The discriminative capacity of journals shows obvious change rules over time and varies in different disciplines. Abstract: This study proposes a method for measuring the discriminative capacity of journals to evaluate and analyze differences in research content among academic journals. A total of 100 Chinese academic journals from five disciplines are selected as research objects. The discriminative capacities of journals in the library, information, and archival science in 2017 and 2013–2017 are calculated and analyzed using bibliographic data (titles, abstracts, and keywords). The characteristics of the discriminative capacities of journals within different time spans are compared based on changes in the spatial distribution and discriminative capacity of the journals. The discriminative capacity of journals published from 2013 to 2017 is determined and ranked to explore their annual change rules over time. The discriminative capacity of journals in five disciplines is calculated and discussed, and the differences among disciplines are measured and analyzed using the mean discriminative capacity. The experimental results reveal that the discriminative capacity of journals in library, information, and archival science evidently vary, with journals in archival science having the highest discriminative capacity, closely followed by journals in information and library science. In addition, the journals show distinct characteristics in different time spans. The discriminative capacity of journals shows obvious change rules over time and varies in characteristics among different disciplines.